OP0237 INTERLEUKIN-17 OR TNF BLOCKADE IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS AFTER WITHDRAWAL OF AT LEAST ONE TNF INHIBITOR. (June 2019) - Tellenbach, Christoph; Micheroli, Raphael; Buerki, Kristina; Scherer, Almut; Nissen, Michael; Zufferey, Pascal; Exer, Pascale; Moeller, Burkhard; Kyburz, Diego; Ciurea, Adrian
Abstract : Background: Secukinumab (SEC), an interleukin-17A inhibitor, is approved for the treatment of ankylosing spondylitis (AS) and has been integrated into the current treatment recommendations of patients with axial spondyloarthritis (axSpA) as an alternative to tumor necrosis factor inhibitors (TNFi). The optimal use of one mode of action over the other remains unclear and longitudinal real-life data are lacking to date. Objectives: To compare drug survival of SEC versus TNFi in axSpA patients having previously stopped at least one TNFi in a large prospective cohort. Methods: Patients with a clinical diagnosis of axSpA in the Swiss Clinical Quality Management cohort were included if they had previously stopped treatment with at least one TNFi, initiated therapy with either SEC or a next TNFi after approval of SEC and had a baseline clinical visit. Drug survival was evaluated by Cox proportional hazards models adjusted for sex, age, Bath ankylosing spondylitis disease activity index (BASDAI), Maastricht ankylosing spondylitis enthesitis score (MASES), proportion of patients with elevated CRP, number of previous TNFi and interaction between mode of action and number of previous TNFi. Results: Baseline characteristics of 382 axSpA patients included (N=107 for SEC and N=275 for next TNFi) are shown in Table 1. The proportion of patients with ≥2 TNFi administered previously was significantly higher in the SEC group. Patients starting SEC had higher baseline disease activity, more enthesitis and greater impairment of spinal mobility, function and quality of life. A history of uveitis was more prevalent in the TNFi group. No differences between the groups could be detected with regards to the reason for discontinuation of the previous TNFi. Unadjusted median (interquartile range) drug maintenance was 1.1 (0.9; 1.3) years for SEC and 2.0 (1.7; 2.2) years for TNFi (p=0.03). The adjusted hazard ratio to stop SEC vs. TNFi in patients without missing data (N=233, 61%) was 1.05 (95% CI 0.42; 2.61; p=0.91) (Table 2). Conclusion: SEC was predominantly initiated in axSpA after use of at least 2 TNFi. Patients starting SEC had a higher mean disease activity than patients starting a next TNFi. Adjusted drug survival after previous withdrawal of TNFi was comparable for SEC or a next TNFi. Acknowledgement: Supported by a grant from Novartis. Disclosure of Interests: Christoph Tellenbach: None declared, Raphael Micheroli: None declared, Kristina Buerki: None declared, Almut Scherer Grant/research support from: Almut Scherer is an employee of SCQM, which receives funding from AbbVie, Celgene, iQONE, Lilly, MSD, Novartis, Pfizer, Roche, Sandoz, Sanofi Genzyme, and UCB., Consultant for: Consultant for Pfizer, MSD, and AbbVie, Michael Nissen Consultant for: AbbVie, Lilly, Novartis, and Pfizer, Pascal Zufferey: None declared, Pascale Exer: None declared, Burkhard Moeller Consultant for: Swissmedic Human Medicines Expert Committee Member (regulatory agency), Diego Kyburz: None declared, Adrian Ciurea Consultant for: AbbVie, Celgene, Janssen-Cilag, MSD, Eli Lilly, Novartis, Pfizer, UCB, Speakers bureau: Abbvie, Celgene, Janssen-Cilag, MSD, Eli Lilly, Novartis, Pfizer, UCB